2023
DOI: 10.3389/fpsyt.2023.1130811
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric rehabilitation patterns in Italy: Results from the Italian Society of Psychosocial Rehabilitation (SIRP) survey

Abstract: IntroductionPsychiatric rehabilitation can be considered a bidirectional technique, designed to allow patients to achieve their personal target, focusing on the individuals’ strengths and challenges related to these targets and also on the community organizations in which they will live them out. Unfortunately, psychiatric rehabilitation is too often not considered a first line treatment. Moreover, rehabilitation has been confused with a generic and rough practice, consisting of extemporary actions and aimless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…39 Psychosocial rehabilitation interventions might be an efficient tool to stimulate resocialization, interpersonal skills, functioning, and autonomy in a patient’s everyday life, bearing in mind that, regardless of their clinical severity, a patient’s areas of functioning can always be improved by therapeutic and rehabilitation work. 40 , 41 Although psychiatric rehabilitation is sometimes considered a second-line treatment, intended as a generic and rough practice, consisting of extemporary actions and aimless entertainments designed to fill “the time passing”, 42 activities and psychoeducation seem to be essential to support the patients both at the onset and at the chronic stage of the disease, promoting mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Psychosocial rehabilitation interventions might be an efficient tool to stimulate resocialization, interpersonal skills, functioning, and autonomy in a patient’s everyday life, bearing in mind that, regardless of their clinical severity, a patient’s areas of functioning can always be improved by therapeutic and rehabilitation work. 40 , 41 Although psychiatric rehabilitation is sometimes considered a second-line treatment, intended as a generic and rough practice, consisting of extemporary actions and aimless entertainments designed to fill “the time passing”, 42 activities and psychoeducation seem to be essential to support the patients both at the onset and at the chronic stage of the disease, promoting mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the recent literature on recovery in schizophrenia, Vita and Barlati 23 argue that an integrated and multifaceted approach involving psychosocial interventions is effective and improves the treatment outcomes of disease. On this regard, the changes in the legislation on mental health care that took place in Italy through Law 180/1978, known as the Basaglia Law, 24 which imposed the closure of asylums and regulated compulsory health treatment, establishing public Mental Health Services, with the intention of favoring therapies that were not detrimental to the dignity and quality of life of patients, have assumed an important role in the evolution of the morals and common sense of civil society in the country.…”
Section: Dovepressmentioning
confidence: 99%
“…Additionally, social skills training has emerged as a promising rehabilitation technique, with evidence suggesting that it can improve social skills, increase social support, enhance selfesteem, and reduce self-stigma, ultimately leading to the improvement of negative symptoms (37)(38)(39). Recent studies have suggested that a combination of multiple intervention methods may be more effective (40)(41)(42), and thus, our study employed a combination of all three intervention methods. The results indicated a significant improvement in negative symptoms, depression, and involuntary movement.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of recovery has been widely discussed in the psychiatric field and is becoming the main target of psychiatric care in many healthcare models (12)(13)(14)(15). However, standardized models of care to facilitate recovery for the main psychiatric diseases are still debated (16,17).…”
Section: Introductionmentioning
confidence: 99%